Safe and Economical Driving Knowledge Vocational School Students in Karangmojo District Gunungkidul Regency - Yayan Setiawan; Rabiman Rabiman; Nurcholish Arifin Handoyono (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research is to find out how high-level safety and economics riding knowledge among students. This Research type is descriptive research. Research instrument uses a multiple choice written test.Â Data analysis technique using descriptive statistic. Research result shows that: 1) The level of safety riding knowledge among students is included in the very high category with an average value 78,81, and 2) The level of economic riding knowledge among students is included in the very high category with an average value 78,81.